Analisis Efektifitas Pengawasan dan Pelayanan Terhadap Produktivitas kerja Tenaga Penyuluh Lapangan (Studi Kasus di Balai Penyuluh Pertanian, Kecamatan Babussalam Kabupaten Aceh Tenggara) - Puspita, Diah Eka; Kuswardani, Retna Astuti; Rahman, Abdul (JURNAL AGRICA, 2011)
In order to develop the resilient agricultural be required the professional agricultural officers, creative , innovative , and trustworthy in the field setting, counseling services and appropriate qualifications and specifications necessary for the development of sustainable agriculture. Productivity is influenced by individual, social work environment, and work conditions factors. Creativity is influenced by encouragement from outside the self, such as control or supervision by the leadership and service provided a relevant agencies. The aims of this study are to analyze (1) the influence of the supervision by the Food Security and Agricultural Counseling (BKPLUH) on the productivity of agricultural instructur, (2) the effect of the service provided by the Food Security and Agricultural Counseling (BKPLUH) on the productivity of agricultural instructur, (3) the influence of supervision and services provided by the Food Security and Agricultural Counseling (BKPLUH)  on the productivity of agricultural instructur. The results shows that the positive effect between control and productivity of 0.269 but is very weak at only 0,072 at 5 percent confidence level. There is a positive effect between BKPLUH services on the productivity of 0.583 and strength are approximately 0.383 with a confidence level of 5 percent. There is positive effect of BKPLUH supervision and services on the work productivity for 0.017 and 0.584. Keywords : Agricultural Counseling, Productivity, Supervision